Effect of magnetic field on aluminium electrodes for production of high efficiency electrolyser - Abdul Syahid Omar, 1990-, author; Saharudin Haron, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper Sarjana Muda Kejuruteraan (Kimia) - Universiti Teknologi Malaysia, 2013